11.0k views
1 vote
Please help asap 50 pts

Please help asap 50 pts-example-1

2 Answers

3 votes

12d^2+4d-1=12d^2+6d-2d-1=6d(2d+1)-1(2d+1)=(2d+1)(6d-1)

Answer: B. (6d - 1)(2d + 1)

User Bala Karthik
by
5.6k points
3 votes
Use the process of elimination.

There is a positive b value and a negative c value, which means that there is a negative factor and positive factor. This eliminates A and C.

Multiply out the factors in B and D:

B
(6d - 1)(2d + 1)
6d * 2d = 12d^2
6d * 1 = 6d
2d * -1 = -2d

12d^2 + 4d - 1

D
(6d + 1)(2d - 1)
6d * 2d = 12d^2
6d * -1 = -6d
2d * 1 = 2d


12d^2 - 4d - 1


The answer is B.
User TorvaldsDB
by
6.0k points